Republic of Armenia : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Armenian government adopted the Poverty Reduction Strategy Paper (PRSP), and the first years of the PRSP implementation have evidently resulted in the significant reduction of both poverty and extreme poverty. The main focus has been sustainable economic growth, institutional reforms, and poverty reduction targeted policy in individual spheres. The annual budget is fully based on the PRSP ideology and was programmed accepting the priorities set up in the PRSP. The government considers the medium-term expenditure framework as a key mechanism to overcome poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet